LEPTIN SERUM LEVEL IN WOMEN WITH OBESITY DO NOT DEFINE LEPTIN CORD BLOOD LEVEL IN THEIR NEWBORNS - OLGA B. Karelina; NATALIA V. Artymuk (Фундаментальная и клиническая медицина, 2017)
Aim. To investigate the serum leptin level in pregnant women either with or without obesity and in their newborns. Materials and Methods. We examined 60 pregnant women with or without obesity (n = 30 per each group) at 38-40 weeks’ gestation along with their newborns following measurement of serum and cord blood leptin level using an enzyme-linked immunosorbent assay.Results. Leptin serum level was significantly higher in obese women compared to those with a normal body weight. Strikingly, the cord blood level of leptin in newborns was lower than in their mothers and did not depend on either maternal body weight or maternal serum leptin level. Conclusions. Serum leptin level in pregnant women is determined by the body weight but does not define cord blood level of leptin in their newborns.